Mapping intrapreneurship through the dimensions of happiness at work and internal communication - Ravina-Ripoll, Rafael; Galván Vela, Esthela; Zorzano Rodríguez, Deisy Milena; Ruíz-Corrales, Missael (My University, 2022)
Purpose This article explores how internal communication impacts happiness at work and intrapreneurship through the dimensions of communication climate and communication in meetings. Design/methodology/approach Literature analysis and quantitative empirical data collection are used to achieve this study's purpose. The study employed a non-experimental, cross-sectional, explanatory design. A questionnaire of closed-ended questions was used, adapted from validated scales for measuring constructs, and apply to 156 employees of industrial, service and commercial companies in the Northeast of Mexico. The analysis techniques used included exploratory factor analysis and structural equation modelling. Findings In the descriptive analysis of the data, the authors find that 57.7% of the sample is satisfied with the communication climate, 28.85% moderately satisfied, and 13.47% dissatisfied. Regarding the levels of happiness at work, high (71.15%), medium (21.15%) and low (7.7%) levels were found. In intrapreneurship, high (67.31%), medium (26.92%) and low (5.77%) levels were found. The exploratory factorial analysis showed that the instrument was adequate for measuring the variables. Good correlations were also found between the items that make up each variable. Finally, the relationship between internal communication, measured by the dimensions of communicative climate and communication in meetings, and happiness at work was verified using the structural equation technique. The latter has a positive impact on intrapreneurship. RESUMEN Objetivo Este artículo explora cómo la comunicación interna impacta la felicidad en el trabajo y el intraemprendimiento a través de las dimensiones del clima de comunicación y la comunicación en las reuniones. Diseño/metodología/enfoque El análisis de la literatura y la recopilación de datos empíricos cuantitativos se utilizan para lograr el propósito de este estudio. El estudio empleó un diseño no experimental, transversal, explicativo. Se utilizó un cuestionario de preguntas cerradas, adaptado de escalas validadas para medir constructos, y aplicado a 156 trabajadores de empresas industriales, de servicios y comerciales del Noreste de México. Las técnicas de análisis utilizadas incluyeron el análisis factorial exploratorio y el modelado de ecuaciones estructurales. Recomendaciones En el análisis descriptivo de los datos, los autores encuentran que el 57,7% de la muestra está satisfecho con el clima de comunicación, el 28,85% medianamente satisfecho y el 13,47% insatisfecho. En cuanto a los niveles de felicidad en el trabajo se encontraron niveles alto (71,15%), medio (21,15%) y bajo (7,7%). En intraemprendimiento se encontraron niveles alto (67,31%), medio (26,92%) y bajo (5,77%). El análisis factorial exploratorio mostró que el instrumento fue adecuado para medir las variables. También se encontraron buenas correlaciones entre los ítems que componen cada variable. Finalmente, se verificó la relación entre la comunicación interna, medida por las dimensiones de clima comunicativo y comunicación en reuniones, y la felicidad en el trabajo mediante la técnica de ecuaciones estructurales. Este último tiene un impacto positivo en el intraemprendimiento.
emeral insight
Keywords: Internal communication; Work happiness; Intrapreneurship; Campus Tijuana